All Things Summed Up Into Christ: On the Christological Impetus of Lesslie Newbigin’s Missional-ecumenical Project - Driel, Edwin Chr. van (Ecclesiology, 2024)
This essay unearths the metaphor from the Epistle to the Ephesians of ‘all things summed up into Christ’ as a critical component of Lesslie Newbigin’s Christology. First, it shows that references to this image form an as yet undetected but consistent line of thought in Newbigin’s work. Second, it argues that the logic of Newbigin’s theological imaginary follows the logic embedded in the Ephesians metaphor. Third, it shows that detecting the particular shape of Newbigin’s Christology allows one to map his project onto wider Christological conversations, and it suggests that one most fruitfully reads him in the context of a supralapsarian Christological approach. Finally, it argues that read in this way, Newbigin’s work can once again make a fresh contribution to the conversation as contemporary practitioners are looking for a new narrative to support their work in this missional era.